Association between early antibiotic treatment after admission and mortality of acute-on-chronic liver failure patients with bacterial infection: A multicenter retrospective study - Xinyi Chen; Wenyi Chen; Jiahang Zhou; Jingyi Chen; Guoqiang Cao; Chenjie Huang; Xiaoqing Lu; Xiaoxiao Chen; Rui Luo; Haijun Huang; Qiaoling Pan; Jinfeng Yang; et al. (Virulence)
Bacterial infection is a significant risk factor in the onset and development of acute-on-chronic liver failure (ACLF). Although early broad-spectrum antibiotic treatment is recommended, the optimal time to initiate antibiotic therapy remains unclear. This study aimed to investigate the relationship between the timing of antibiotic treatment and the prognosis of ACLF patients with bacterial infection. Patients with ACLF and bacterial infections upon admission were retrospectively evaluated. The predictors of 28-day mortality were identified using univariate, least absolute shrinkage and selection operator regression analysis, and multivariate logistic regression analyses. The “survminer” R package was used to categorize patients into two groups based on a 6-h threshold: early antibiotic administration (<6 h of admission) and later antibiotic administration (≥6 h after admission). A total of 295 patients were evaluated. The lungs were the most common site of infection (61.7% of patients had lung infections), followed by the peritoneum (25.4% of patients had spontaneous bacterial peritonitis). The time to first antibiotic administration was an independent predictor of 28-day mortality, and the odds of mortality increased by 2% for each hourly delay in antibiotic administration after admission. In Kaplan-Meier survival analysis, both 28-day and 90-day mortality rates were significantly lower in the early antibiotic group than in the later antibiotic group (both p < 0.0001). In conclusion, early antibiotic treatment is an independent predictor of 28-day mortality in ACLF patients with bacterial infections. Patients who received antibiotics less than 6 hours after admission exhibited lower 28- and 90-day mortality rates.